2020
DOI: 10.1563/aaid-joi-d-19-00201
|View full text |Cite
|
Sign up to set email alerts
|

The Biomaterial-Induced Cellular Reaction Allows a Novel Classification System Regardless of the Biomaterials Origin

Abstract: Several different biomaterials are being introduced for clinical applications. However, no current material-specific systematic studies define parameters for evaluating these materials. The aim of this retrospective animal study is to classify biomaterials according to the in vivo induced cellular reaction and outline the clinical consequence of the biomaterial-specific cellular reaction for the regeneration process. A retrospective histologic analysis was performed for 13 polymeric biomaterials and 19 bone su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…Different studies have pointed out the importance of biomaterial-specific physicochemical characteristics essential for inducing the inflammatory response [ 12 , 13 ]. Based on these facts, a recent study suggested a new classification of biomaterials according to the induced cellular reactions and the formation kinetics of MNGCs by analyzing the cellular reactions of up to 29 different materials in a subcutaneous implantation model for 30 days [ 25 ]. The authors suggest three classes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Different studies have pointed out the importance of biomaterial-specific physicochemical characteristics essential for inducing the inflammatory response [ 12 , 13 ]. Based on these facts, a recent study suggested a new classification of biomaterials according to the induced cellular reactions and the formation kinetics of MNGCs by analyzing the cellular reactions of up to 29 different materials in a subcutaneous implantation model for 30 days [ 25 ]. The authors suggest three classes.…”
Section: Discussionmentioning
confidence: 99%
“…The authors suggest three classes. Class I included biomaterials that did not induce any MNGCs at any time point [ 25 ]. Class II represented biomaterials that induce an initial number of MNGCs and maintain a sustained number over 30 days, while class III included biomaterials that induce a continuously increasing number of MNGCs over 30 days.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the induction of MNGCs by different biomaterials, our group recently proposed the classification of these biomaterials into three distinct groups [39]. Class I represents those biomaterials that does not induce MNGCs throughout the implantation period (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Multinucleated giant cells (MNGCs) appear as a reaction to implanted biomaterials 41‐43 . The number of these cells and their persistence greatly influence the further inflammation course of the tissue and healing outcome and are greatly dependent on the physico‐chemical properties of implanted biomaterials 41,42,44 . These cells are also very important in regeneration and healing process since they are involved in the biodegradation of the biomaterial and are related to expression of both pro‐ and anti‐inflammatory molecules, which represent signals for other cells and events that lead to tissue regeneration 41,42 .…”
Section: Discussionmentioning
confidence: 99%